PENGENALAN METODE HIDROPONIK SEBAGAI UPAYA PENGEMBANGAN BUDIDAYA TANAMAN SELADA PADA MASYARAKAT DESA MASALAP RAYA KECAMATAN RANTAU PULUNG - Widyanti, Eka; Nurhaeni, Nurhaeni; Yusuf, Hendri; Putri Kumalasari, Febriana; Jumrianah, Jumrianah (El-Madaniyah : Jurnal Pengabdian Masyarakat, 2024)
Year after year, month after month, technological developments are increasingly rapid, especially in the agricultural sector, so that people who are not updated about technology will be left behind in information so that the methods they use are only the same, which causes no increase in maximum profits. Hydroponics is one of the right technologies to know, because currently most of the land is used in the service and industrial sectors so that agricultural activities directly on the land do not run as conducively or as they should. Thus, with limited land, hydroponic planting technology is expected to be an alternative for using yards as a source of maximum plant production. Hydroponics is a planting method that is used without soil, hydroponics uses media in the form of nutrients A and B, oxygen, water, rock wool. Perlite, cocopeat, etc.